(untitled) (University of Khartoum Engineering Journal, 2021)
Additive manufacturing (AM) is the technology used to manufacture products directly by layering the material, so no special tools are needed to produce the parts. AM is favoured by the producers since it is cost-effective when it is used for small production volumes, leading to ease in the customization of products. Previous attempts had been made to develop a cost model for AM. However, most of these attempts did not consider the quality cost. The model developed by Schmid and Levy was the first cost model focusing on the quality cost of AM, they found that quality cost of AM may reach up to 16% of total manufacturing cost. The current research made a further investigation on quality cost. As a result, a detailed cost model for all AM technologies was made. The developed model considered all quality aspects along the AM process chain. The developed model was then used to calculate the quality cost when building several copies of a part; it was found that quality cost was about 20% of the total manufacturing cost. The work then focused on investigating the effect of making replacements for defect parts; this investigation revealed that it was better always to make replacements than just dispose of the defects. Finally, the study recommends the study of the exact effect of applying quality control activities on the percentage of defects, so a precise prediction for the quality cost may be attained. Another recommendation is to extend the detailed cost model for all AM technologies, considering the specific variables in each one